KONSEP DASAR PENGELOLAAN DI KELOMPOK BERMAIN AMALIA - Mefia, Yolanda Arta; Wulandari, Retno (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
In this study, we will discuss the Basic Concepts of Playgroup Management which are important in carrying out activities in an institution. This study aims to describe the planning, organizing, implementation, supervision and assessment of the play group. This research uses a descriptive method with a qualitative approach, while the subjects of this study include administrators and students. Data collection techniques used are interviews, observation, and documentation. The results of this study are to find out more about the management of Playgroups. Managers will always measure the development and success of children's education by looking at the extent of the benefits that have been provided and future improvements. Managers will contribute so that the program management organized provides benefits in accordance with the vision and mission of the institution. The benefits for educators are to provide enthusiasm to always work optimally and provide professional educational services, education will realize that the role carried out will have an impact on the success of being a role model that is always followed by students.